If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-8x-4=12
We move all terms to the left:
6x-8x-4-(12)=0
We add all the numbers together, and all the variables
-2x-16=0
We move all terms containing x to the left, all other terms to the right
-2x=16
x=16/-2
x=-8
| 4(x+6)=4(x+7) | | 8n-5=-19(12+n) | | 8a+12=80 | | 10x-8=20-14x | | V=1/3πr^2 | | 6f=-66 | | 5(x+5)=5x-1 | | 5n+-4n=5 | | -12+2x=-14 | | 5-x-x=- | | 3v-42=5(v-6) | | 2n-13=-19(16+4n) | | a/9=1/23 | | 289=69-u | | 2(x-2)=5x-16 | | -30=12-6x | | 5/8=3/y | | 6x+12+7x=-4 | | -2(x^2-7)^2+3=-47 | | 4(k+9)=4(k+9) | | −4−0.2x+11=−0.8x+10 | | 5x−7=58 | | −4−0.2x+11=−0.8x+10 | | 5x−2=3x+1 | | 12=0.005x | | 116(x−40)=5+x | | 11-3a+6=27 | | 5(x−2)=3x+1 | | 6(x+6)=6x+4 | | −5(3x−15)=2(x−1)−59 | | 10h+4=11 | | 7b^2+3b+42=0 |